Structure, Process, and Quality Indicators for Pressure Injury Prevention and Care in Austrian Hospitals: A Quality Improvement Project. Issue 6 (November 2019) - Hoedl, Manuela; Eglseer, Doris; Lohrmann, Christa
Abstract : The purpose of this quality improvement point-prevalence project conducted in 2017 was to describe the structure, process, and outcome indicators for pressure injury (PI) prevention and care in 37 Austrian hospitals with 208 wards and 2955 patients, with an average age of 66 years. Structural indicators such as PI guideline availability were measured on hospital and ward levels. On the process level, patients were assessed to determine whether PI interventions such as mobilization or use of moisturizer/barrier cream were implemented. On the outcome level, data on the presence of hospital-acquired PIs based on skin inspection were collected. These data were collected using the Austrian version of the National Prevalence Measurement of Care Problems, a standardized survey. Structural level results showed PI protocols or guidelines were available in 75.7% of the participating institutions. Staff education such as refresher courses was seldom available on the ward level (46.6%). Process-level results indicated the most commonly applied intervention in both patients at risk of or had a PI was the use of skin-protectant moisture barrier creams (63.1% and 85.2%, respectively). Patients with PIs also frequently received interventions focusing on the heels (72.9%) and mobilization (69.2%). With regard to the outcome level, the overall and hospital-acquired PI prevalence rates were 3.6% and 1.3%, respectively. We recommend focusing on staff, patient and family education including the prevention and treatment of hydration and nutritional deficits, an uncommonly used intervention in Austria based on these data, to improve the quality of PI prevention and care in the hospital setting.